Evaluation of the scientific impact of the Ebola epidemic: a systematic review. (June 2018) - Mutters, N.T.; Malek, V.; Agnandji, S.T.; Günther, F.; Tacconelli, E.
Abstract: Objectives: The Ebola outbreak prompted an extensive number of scientific publications, but little attention has been paid to the involvement of local scientists, distribution of research funding and related publications. We sought to systematically review publicly available information on the scientific impact of the Ebola epidemic. Methods: A systematic review of literature on the Ebola outbreak was performed. Extracted information included origins of the authors, type and distribution of funding, and impact factors (IF) of related publications between 6 December 2013, and 22 December 2015. Results: We identified 460 relevant articles out of 3281 references, which were mostly authored by American (46.6%) and European (28.4%) institutions; only 13.4% of authors were affiliated with African institutions. Most IF can be attributed to the Americas and Europe, with 43% (25 030.8 IF) and 34.5% (20 074.2 IF), respectively, compared with 17.9% (10 436.5 IF) in Africa. Funds were provided mainly by the Americas (31.8% of all funded studies) and Europe (17%). American and European funds were also distributed back, mainly to American (77.8%) and European (85.2%) institutions, respectively. Conclusions: The Ebola outbreak had a significant scientific impact and resulted in numerous publications in high IF journals. The main impact could be measured in the Americas and Europe, and was directly related to funding. African researchers were only marginally involved in the scientific processing (86.6% of all researchers were not African), probably because major research centres are located in America and Europe. Our results suggest the importance of promoting closer cooperation between regions.